2017
DOI: 10.5194/hess-21-2725-2017
|View full text |Cite
|
Sign up to set email alerts
|

Saturated hydraulic conductivity model computed from bimodal water retention curves for a range of New Zealand soils

Abstract: Abstract. Descriptions of soil hydraulic properties, such as the soil moisture retention curve, θ (h), and saturated hydraulic conductivities, K s , are a prerequisite for hydrological models. Since the measurement of K s is expensive, it is frequently derived from statistical pedotransfer functions (PTFs). Because it is usually more difficult to describe K s than θ (h) from pedotransfer functions, Pollacco et al. (2013) developed a physical unimodal model to compute K s solely from hydraulic parameters derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Assouline and Or (2013) review numerous expressions for the saturated hydraulic conductivity. Interestingly, approaches have emerged to estimate the saturated hydraulic conductivity from the retention curve parameters Pollacco et al, 2013Pollacco et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Assouline and Or (2013) review numerous expressions for the saturated hydraulic conductivity. Interestingly, approaches have emerged to estimate the saturated hydraulic conductivity from the retention curve parameters Pollacco et al, 2013Pollacco et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the presented double prediction hyPTF does not alleviate problems mentioned in the literature relating to unconsidered effects of stone content on SHPs (Nasri et al, 2015;Tetegan et al, 2015), on organic (Wallor et al, 2018), forest (Puhlmann & von Wilpert, 2012), or multimodal soils (Pollacco et al, 2017). In addition, the effects of dynamic nonequilibrium Šimůnek & van Genuchten, 2008) and macropore flow are not captured, since in the sense of the BW-VGM model, only an application to matrix flow is possible.…”
Section: 1029/2019wr026820mentioning
confidence: 85%
“…Previous work has shown that the S SA of soil is closely dependent upon the soil texture and could be estimated from the soil properties and PSD (Sepaskhah and Tafteh, 2013;Resurreccion et al, 2015). The method used to estimate the S SA in Sect.…”
Section: The Effects Of the Estimated S Samentioning
confidence: 99%
“…The soil water retention curve (SWRC), which represents the relationship between the water pressure and water content, is fundamental to researching water flow and chemical transport in unsaturated media (Pollacco et al, 2017). Direct measurements of the SWRC consume both time and money (Arya and Paris, 1981;Mohammadi and Vanclooster, 2011), while estimating the SWRC from the particle size distribution (PSD) is both rapid and economical.…”
Section: Introductionmentioning
confidence: 99%